Can Temporary Wage Incentives Increase Formal Employment? Experimental Evidence from Mexico - Martin Abel; Eliana Carranza; Kimberly Geronimo; Maria Elena Ortega (Institute of Labor Economics (IZA), 2022)
Formal sector entry-level jobs in Mexico offer low starting salaries but substantial wage growth. This paper experimentally tests whether a six-months wage incentive can increase formal employment among secondary school graduates. Combining survey and high-frequency social security data, the paper shows that the incentive increases formal employment among vocational school graduates by 4.2 percentage points (14.5 percent) over the first two years driven by a 5 percentage point (25 percent) increase in permanent formal jobs. These employment gains are due to both extensive and intensive margin effects. Treatment effects are concentrated among youths with binding reservation wages who also tend to underestimate formal wage growth.
Keywords: J08; J24; J41; J46; J63; 330; youth employment; wage subsidy; formal employment; reservation wages